Pengaruh Literasi Keuangan dan Inklusi Keuangan terhadap Kinerja UMKM dengan Debt Financing sebagai variabel Mediasi - Haikal, Fahri; Olivia, Putri Sarah; Diandra, Didip; Sulistianto, R Hario; Azhari, Muhammad Zakky; Mustofa, Yusufi Arif (Jurnal Penelitian Ekonomi Akuntansi, 2025)
This study aims to analyze the effect of financial literacy and financial inclusion on the performance of MSMEs, with debt financing serving as a mediating variable. Using a survey of 200 MSME owners across various business sectors, data were processed and analyzed through Structural Equation Modeling (SEM) to test both direct and mediating effects. The findings indicate that financial literacy and financial inclusion have a significant impact on MSME performance, both directly and indirectly, through debt financing. This highlights the importance of financial knowledge and access to credit as drivers of sustainable business growth. The novelty of this research lies in positioning debt financing as a mediating factor that bridges financial capacity with performance outcomes, which has received limited attention in prior MSME studies. The study implies that improving financial education and expanding financial inclusion programs can enhance MSME resilience, while promoting responsible debt financing as an effective mechanism to strengthen business sustainability and competitiveness in the digital economy era.This study is limited to MSMEs in a specific region and cross-sectional data; future studies are encouraged to expand regional coverage, incorporate additional variables, and apply longitudinal approaches.